Collection, extraction, fractionation and isolation of phytochemical constituents of hedyotis diffusa / Muhammad Dzulfadli Rohaizad - Rohaizad, Muhammad Dzulfadli (2008)
Hedyotis diffusa, traditional Chinese medicines consist of complex constituents. Thus it requires a proper analytical technique for their rapid and simultaneous analysis. The main objective of this study is fractionation and isolation of compound from this herb. Generally the methods used involved extraction, fractionation, isolation and compound analysis. Initially, compound of interest was obtained through fractionation of n-hexane extract by using Thin Layer Chromatography (TLC) technique. Next the compound was purified by preparative TLC. Eventually, the pure compound of interest was subjected to Nuclear Magnetic Resonance (1H-NMR) analysis to identify the real structure of the compound. Based on interpretation of NMR spectra, the compound of interest is suspected as ursolic acid. But we failed to obtain enough evidence to prove it as ursolic acid as the quantity of compound was not sufficient and adequate for further 13C-NMR and 20-NMR analysis. However, throughout this study we managed to detect several unknown compounds by using TLC technique. Further study need to be conducted to identify those unknown compounds,